Potentials of Guinea Grass (Panicum maximum) as Forage Crop in Livestock Production - Aganga, A.A.; Tshwenyane, S. (Pakistan Journal of Nutrition, 2003)
Panicum maximum (guinea grass) is native to Africa but this grass was introduced to almost all tropical countries as a source of animal forage. It grows well on a wide variety of well drained soils of good fertility and it is suitable to stop soil erosion. It can survive quick moving fires which does not harm the underground roots and drought because of the deep, dense and fibrous root system. Guinea grass is a clump-forming perennial which grows best in warm frost free areas receiving more than 900 mm rainfall. Crude protein (CP) content of fresh guinea grass varied from 5.0 to 5.6% while guinea grass silage contains 5.0 to 5.5% CP. The digestibility (IVDOM) varied with the variety from 56.9% for Gatton to 87.7% for Vencidor. This paper reviews the potential of P. maximum as a forage for animal production in the tropics and Sub tropics.